Refractory or relapsed aggressive B-cell lymphoma failing (R)-CHOP: an analysis of patients treated on the RICOVER-60 trial. - Glass, B.; Dohm, A. J.; Truemper, L. H.; Pfreundschuh, M.; Bleckmann, A.; Wulf, G. G.; Rosenwald, A.; Ziepert, M.; Schmitz, N. (Ann Oncol, 2017)
BACKGROUND: The prognosis of elderly patients with aggressive B-non-Hodgkin's lymphoma after first lymphoma-related treatment failure (TF-L) is not well described. METHODS: We analysed patient characteristics including the presence of MYC rearrangements and MYC-expression immunohistochemistry (IHC) at diagnosis and modalities of salvage therapy and their impact on the prognosis of patients between 61 and 80 years who had been treated on the RICOVER-60 trial. RESULTS: TF-L occurred in 301 of the 1222 (24.6%) patients; 297 patients could be analysed. Prognosis was extremely poor in patients with primary progressive disease or early relapse (</=12 months) with median survivals of 3.3 and 6.4 months. Survival after TF-L was significantly lower in patients pretreated with R-CHOP compared with CHOP (23.0% versus 36.4% at 2 years, P = 0.016). In patients with MYC translocation at diagnosis Rituximab reduced the risk of TF-L from 58.8% to 26.3%. Survival after TF-L was significant longer for patients after CHOP without MYC translocations (31.8% versus 0% at 2 years, P < 0.001) or negative MYC-IHC (41.0% versus 16.8% at 2 years, P = 0.017) but not after R-CHOP. 224 patients (75.4%) received salvage therapy. Rituximab was part of salvage therapy in 57.4% and improved 2-year survival rate from 20.7% to 46.8% (P < 0.001). The benefit of R was significant after first-line CHOP [2-year overall survival (OS) 49.6% versus 19.1%, P < 0.001] as well as after R-CHOP (2-year OS 33.1% and 22.5%, P = 0.034). For patients pretreated with R-CHOP long-term survival was below 15% regardless of the treatment chosen. CONCLUSION: MYC rearrangement and IHC are adverse prognostic factors after TF-L for CHOP treated patients, rituximab as part of first-line therapy reduced the effects of MYC-break. Rituximab improves results of any type of salvage therapy; however, survival after progression/relapse of aggressive B-cell lymphoma in elderly patients pretreated with (R)-CHOP is poor regardless of treatment chosen.
Keywords: Age Factors; Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/administration & dosage; Antineoplastic Combined Chemotherapy Protocols/administration & dosage/*therapeutic use; Cyclophosphamide/administration & dosage; Doxorubicin/administration & dosage; Female; Humans; Immunohistochemistry; Lymphoma, B-Cell/*drug therapy/genetics/metabolism; Male; Middle Aged; Prednisone/administration & dosage; Proto-Oncogene Proteins c-myc/biosynthesis/genetics; Retrospective Studies; Rituximab/administration & dosage; Salvage Therapy; Vincristine/administration & dosage